Leadership Style of Village Heads in Village Infrastructure Development - Kusuma Wijaya, Danny; Usrotin Choiriyah, Ilmi (Indonesian Journal of Public Policy Review, 2022)
The village head of Plabuhanrejo carried out a program that focused on village development, such as the construction of retaining walls and road rebates. However, the village head was still unable to mobilize village youth to participate in the deliberation held in Plabuhanrejo Village. The purpose of this study was to describe and analyze the leadership style of the Village Head in the implementation of infrastructure development in Plabuhanrejo Village. The research method used descriptive qualitative with interview, observation and documentation data collection techniques. Determination of informants using purposive sampling technique. Data analysis techniques in data collection, data reduction, data presentation and drawing conclusions. The results of this study, the village head's decision-making ability has a role in determining a decision. In communication skills, the village head does not yet have good communication with the youth in Plabuhanrejo Village. while the ability to control subordinates, the village head provides sanctions for subordinates who are not disciplined at work.